Organisational culture and the experience of negative emotions on counterproductive workplace behaviours - Johnson, Cheron Chanelle (My University, 2016)
The aim of this study was to explore whether the experience of negative emotions in the workplace mediated the relationship between organisational culture and counterproductive workplace behaviours (CWBS). Organisational culture in this study was specifically studied from an ethical perspective. This was of particular interest, since previous research endeavours have predominantly explored predictors of CWBs from an individual level of influence. Such a focus has consequently ignored the role of the situation/organisation as a determinant of employees’ behaviour in organisations. This largely overlooked focus has in turn, rendered recommendations for practice relatively ineffective. Therefore, in light of the literature’s current state, it was of particular interest to explore factors predictive of CWBs from both the individual and situational areas of influence in this study. More specifically, this study sought to investigate if organisational culture with particular reference to ethical quality predicted CWBs, and whether the experience of negative emotions in the workplace had any bearing on how an ethical organisational culture related with CWBs. To explore this area of interest, this study consisted of one hundred and fifty three participants from various organisations in the area of Johannesburg. Each participant was presented with a questionnaire that consisted of the Job-related Affective Wellbeing Scale (JAWS), the Corporate Ethical Virtues Scale (CEVS) and the Unethical Behaviour Scale (UBS). The results of this study were analysed using the statistical techniques of multiple regressions, Sobel tests, and Baron and Kenny’s four step process of testing for mediation. Findings obtained in this study revealed that organisational culture (lacking an ethical quality) and the experience of negative emotions both significantly predicted the likely occurrence of CWBs. In addition, findings from mediation analyses indicated that employees’ experience of negative emotions in the workplace, partially mediated the relationship between organisational culture and CWBs. Thus, the ethicality of an organisation’s culture had both a direct and indirect effect on the occurrence of CWBs. The indirect effect of organisational culture on CWBs was explained through the experience of negative emotions in the workplace. In other words, the direct effect of organisational culture on CWBs suggests that when an organisation’s culture lacks ethical quality, then the occurrence of CWBs may be more likely. In addition, the indirect effect of employees’ experience of negative emotions in the workplace on the relationship between organisational culture and CWBs, suggests that an organisation’s culture that lacks ethical quality may more likely result in the experience of negative emotions in the workplace, which in turn is positively related with the occurrence of CWBs. Thus, having explored predictive factors of CWBs from both an individual and organisational level of influence has enabled this study to contribute to the research domain of CWBs which has largely been overlooked in previous studies. In this study, the dual area of influence has shown to be very significant as it has given greater insight into employee workplace behaviours such as CWBs. This study concludes with reporting on the limitations encountered during the process of research and also gives due consideration to the implications presented by findings obtained. Furthermore, a few recommendations for practice are proposed and directions for future research endeavours in the organisational behaviour domain are suggested.
A research report submitted in partial fulfillment of the requirements for the Degree of Masters by Coursework and Research Report in the field of Industrial Psychology in the faculty of Humanities, University of the Witwatersrand, 26 June 2015